Character and Competence in The Implementation of Living Curriculum in Indonesian Schools Kuala Lumpur - Fa’uzobihi, Fa’uzobihi; Suseno, Muchlas; Supriyati, Yetti; Ismuni, Mutdi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This article explains the concept of Living curriculum in the world of education which has implications for character and skills through the process of coaching and habituation of students about the values, goals and meaning of life. Through this curriculum students can realize how important it is to behave based on good rules and values. The Life Curriculum is also an activity to develop or strengthen the character and good values possessed by students, this makes students have complex principles for harmonious relationships between humans and their environment. The method used in this study is descriptive analysis, which collects data from several national and international articles related to the living curriculum.